Greening Industries in Ethiopia: Analysis of Laws and Overview of Compliance in Three Industrial Parks - Tesfaye Abate Abebe (Mizan law review, 2024)
Ethiopia has been developing industrial parks to promote development. Industrial park development process is regulated by international and domestics laws and it envisages green development or sustainable industrial parks. This article investigates the Ethiopian laws and the practices in Bole Lemi I, Kombolcha and Hawassa industrial parks. The methodology of the research mainly focused on laws and some empirical research through interviews, questionnaires, and observation to gather primary data from the three industrial parks as insights to industrial parks under comparable circumstances. The finding reveals that there are legal gaps in environmental standards such as absence of plastic-waste management that ensures green industrial development. There are also gaps relating to the right to fair wage for the workers in the industries under study. The relevant regulatory organs are thus expected to pay due attention to these gaps that should be addressed in tandem with the standards and the path required in sustained economic win-win benefits to investors, employees, and the public in the context of inclusive development and environmental sustainability.